Additional information from array comparative genomic hybridisation technology over conventional karyotyping in prenatal diagnosis–a systematic review and meta-analysis. (16th November 2010) - Hillman, SC; Pretlove, S; Coomarasamy, A; McMullan, D; Davison, EV; Maher, E; Kilby, MD
Abstract : Background: Array comparative genomic hybridisation (array CGH) is transforming clinical cytogenetics with its ability to interrogate the human genome at increasingly high resolution. Objective: To determine whether array CGH testing in the prenatal population provides diagnostic information over conventional karyotyping. Search Strategy: MEDLINE (1970 to December 2009), EMBASE (1980 to December 2009) and CINAHL (1982 to December 2009) were searched electronically. Selection criteria Studies were selected if array CGH was used on prenatal samples or where array CGH was used on postnatal samples following termination of pregnancy for structural abnormalities detected on an ultrasound scan. Of the 135 potential articles, 10 were included in this systematic review. Data Collection and Analysis: Results from the chromosome analysis and array CGH analysis were extracted. The pooled rate of extra information detected by array CGH when the prenatal karyotype was normal and conversely the pooled rate of extra information from karyotyping when the array CGH was normal was calculated. Main Results: Array CGH detected 3.6% (95% CI 1.5% to 8.5%) additional genomic abnormalities when conventional karyotyping was 'normal' regardless of referral indication. This increased to 5.2% (95% CI 1.9% to 13.9%) more than prenatal karyotyping when the referral indication was a structural malformation detected on ultrasound scan. Conclusion: There appears to be an increased detection rate of chromosomal abnormalities when array CGH techniques are employed in the prenatal population over conventional karyotyping. However, some of these are copy number imbalances that are not clinically significant. This carries implications for prenatal counselling and maternal anxiety.